The 2018 northern European hydrological drought and its drivers in a historical perspective - S. J. Bakke; M. Ionita; L. M. Tallaksen (Hydrology and Earth System Sciences, 2020)
In 2018, large parts of northern Europe were affected by an extreme drought. A better understanding of the characteristics and the large-scale atmospheric circulation driving such events is of high importance to enhance drought forecasting and mitigation. This paper examines the historical extremeness of the May–August 2018 meteorological situation and the accompanying meteorological and hydrological (streamflow and groundwater) drought. Further, it investigates the relation between the large-scale atmospheric circulation and summer streamflow in the Nordic region. In May and July 2018, record-breaking temperatures were observed in large parts of northern Europe associated with blocking systems centred over Fennoscandia and sea surface temperature anomalies of more than 3 ∘ C in the Baltic Sea. Extreme meteorological drought, as indicated by the 3-month Standardized Precipitation Index (SPI3) and Standardized Precipitation Evapotranspiration Index (SPEI3), was observed in May and covered large parts of northern Europe by July. Streamflow drought in the Nordic region started to develop in June, and in July 68 % of the stations had record-low or near-record-low streamflow. Extreme streamflow conditions persisted in the southeastern part of the region throughout 2018. Many groundwater wells had record-low or near-record-low levels in July and August. However, extremeness in groundwater levels and (to a lesser degree) streamflow showed a diverse spatial pattern. This points to the role of local terrestrial processes in controlling the hydrological response to meteorological conditions. Composite analysis of low summer streamflow and 500 mbar geopotential height anomalies revealed two distinct patterns of summer streamflow variability: one in western and northern Norway and one in the rest of the region. Low summer streamflow in western and northern Norway was related to high-pressure systems centred over the Norwegian Sea. In the rest of the Nordic region, low summer streamflow was associated with a high-pressure ...